Institutional and Legal Framework of Anti-Doping in Bosnia and Herzegovina: Balancing Sport Integrity and the Athlete’s Right to a Fair Hearing - Alihodžić, Jasmina; Duraković, Anita (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
This article examines the institutional and legal framework for resolving anti-doping cases in Bosnia and Herzegovina, focusing on the balance between safeguarding the integrity of sport and protecting athlete's right to a fair hearing. Despite the country’s complex constitutional structure, the primacy of international law and explicit provisions in the national Sports Law ensure full compliance with the WADA Code. Particular attention is devoted to the de novo review before the CAS, which guarantees a complete reassessment of facts and law in relation to the first instance bodies. The analysis highlights the role of the national Anti-Doping Agency, disciplinary panels and CAS mechanisms, emphasizing procedural safeguards. By situating Bosnia and Herzegovina within an international context, the study demonstrates how coherent governance structures can simultaneously uphold clean sport and protect fundamental rights of athletes.